Impact of a Mental Health Gap (mhGAP) Module on Behavioral and Psychological Symptoms of Dementia (BPSD) and Caregiver Burden in a South Indian Community - Thasleem SK; Sharma R; Shaji KS (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Non pharmacological interventions are the first line treatment recommended for behavioraland psychological symptoms of dementia and mental health gap module is a non-pharmacologicalinterventions based program developed by Word Health Organization for dementia patients especially inlow and middle income countries. This study was conducted to evaluate the impact of mental health gapmodule on Behavioral and psychological symptoms of dementia and caregiver burden in a south Indian ruralcommunity.Methods: A quasi experimental one group pretest posttest time series design study was conducted among61 elderly with dementia in a south Indian rural community who were selected using purposive sampling.Pre interventional assessment was done with Neuropsychiatric Inventory Questionnaire and Zarit BurdenInterview. A multifaceted mental health gap intervention was delivered to the patients through monthly homevisit by community health workers for one year and impact on behavioral and psychological symptoms andcaregiver burden was tested at six weeks, three months and 12 months.Conclusion : There was a significant improvement in behavioral and psychological symptoms of dementiaand caregiver burden during study period. This study proved that behavioral and psychological symptomsof dementia and caregiver burden can be managed though home based non pharmacological interventionsusing community health workers which is a beneficial and cost effective model for low and middle incomecountries.